Teacher educators' simplex system in navigating the process of responding to disruptive education – a case from Qatar. Issue 2 (3rd April 2022) - Al-Thani, Hessa; Chaaban, Youmen; Du, Xiangyun
ABSTRACT: The study explored teacher educators' experiences in navigating the process of responding to disruptive education due to the COVID 19 pandemic. From a complexity theory lens, the concept of simplex system was used to examine three teacher educators' narratives on their teaching experiences prior to, during and post pandemic, as they responded to institutional top-down policy mandating the emergency shift from face-to-face to full-scale synchronised online teaching. Findings of the study suggested that the teacher educators all struggled within the intrapersonal space, consisting of beliefs, motivation, efficacy and emotions during the emergent transition to full-scale online teaching, while they also experienced change of interpersonal relationships with students and colleagues. The study also revealed variations in their individual coping strategies for self-organisation in response to the emergent policy change, utilising their individual sources and prior experiences. The study called for the need to better understand teacher educators' simplex system at both the individual level and institutional level. Further, it was highly recommended that teacher educators become actively involved in the policy making process and communications; in order to enhance their understanding of complex situations and support their agentic actions in accomplishing their goals.